Synthesis of new safrol derivatives by modifying the side chain - Loc, Tran Van; Sung, Tran Van (Vietnam Journal of Chemistry, 2014)
By modifying the side chain with different eights derivatives of safrol have been synthesized functional groups. All obtained compounds are new and their structures are assigned by mass analysis and NMR spectra